PENGETAHUAN DAN PELATIHAN FIRST AID TERHADAP PENINGKATAN KOMPETENSI MASYARAKAT X - Noviyanti Noviyanti; M. Kafit (Institut Kesehatan dan Teknologi Al Insyirah, 2023)
First Aid, more commonly known as first aid in accidents (P3K), really needs to e known by everyone. The lack of competence in the community in preventing secondary injuries that often accompany victims is actually the main cause of death. This study aimed to determine community knowledge and First Aid Training on Increasing Community Competence X. Analytical quantitative research methods, and case studies. The population is Community X as many as 30 people were selected to be given training and all of them are used as samples (Total Sampling). The instrument used was a questionnaire with closed and open questions. The analytical test used Chi-square. The results of the study found that knowledge has a Pvalue of 0.018 and First aid training has a Pvalue of 0.026. Conclusion There is a significant influence between knowledge and frist aid training on increasing the competence of community X with Pvalue < α =0.05. suggestions for community X to apply the knowledge gained when dealing with victims who must be given first aid by following the directions that have been conveyed when attending the training. Keywords: knowledge, Training, First Aid, Competence